The ANALISIS KESESUAIAN MATERI BUKU TEKS BAHASA INDONESIA TERHADAP CAPAIAN PEMBELAJARAN (CP) KURIKULUM MERDEKA: Analisis Materi terhadap Capaian Pembelajaran - AHMAD, MUHLIS; Kuntarto, Eko; Purba, Andiopenta (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Abstract The existence of textbooks cannot be separated from the curriculum that is implemented. When the old curriculum is replaced, the content or material of the textbook must be adapted to the new curriculum. This research aims to determine the level of suitability of the Indonesian language textbook material for class X or Phase E SMA/SMK are used, against the learning outcomes (CP) determined by the Assessment and Education Curriculum Standards Agency of the Ministry of Education and Culture of the Republic of Indonesia in implementing the Independent Curriculum. These learning outcomes are divided into four language skills elements which include listening skills elements, reading and viewing skills elements, speaking and presentation skills elements, and writing skills elements. The research design uses descriptive analysis research. The data source used in the research is an Indonesian language textbook entitled Smart, Smart in Indonesian Language and Literature for Class X SMA/SMK, published in 2021 by the Ministry of Education and Culture. The results of this research concluded that the material presented was very appropriate to the learning outcomes (CP) of Indonesian language subjects.